A OPTIMIZING CHILDREN'S INTELLIGENCE WITH STORYING ACTIVITIES IN KRATONAN, SERENGAN, SURAKARTA - Lailla Hidayatul Amin; Mu’in Abdullah Mu’in Abdullah; Alfian Eko Rochmawan Alfian Eko Rochmawan; Abdullah Hasan At Taufiqi Abdullah Hasan At Taufiqi (Salwatuna : Jurnal Pengabdian Masyarakat, 2022)
Intelligence cannot be measured only based on academic intelligence tests or IQ, but by looking at a person's ability to solve every problem (problem solving) and the ability to create new products that have cultural value (creativity). This storytelling activity took place in RW 01 and 02 Kratonan and was held on February 23, 2022, with 60 children participating. This activity aims to optimize children's intelligence through fairy tales, provide knowledge of learning based on multiple intelligences in children's education, and apply learning based on multiple intelligences for children. With this intelligence, students can adapt and learn from experience. The results of the activity show that storytelling can develop children's intelligence and fairy tales can be used as a medium to tell something to children orally or give them a message. In storytelling, it can increase imagination and can shape its character and for creative children it will be easy to guess what will happen next to the fairy tale character. Fairy tales can make children active, love to read and can make children know the good things and avoid the bad things.